Needs analyses for Task-Based curriculum design: How useful can it be for general purpose L2 courses? - Liakina, Natallia; Michaud, Gabriel (Nouvelle Revue Synergies Canada, 2018)
When designing a task-based language curriculum, it is essential to conduct a needs analysis (NA) to gain insight into the needs and goals of the student population (Long SLA and TBLT 6). This article illustrates the steps of the process by which an NA was designed and implemented in two university-level B2 level oral communication French as a Second Language courses to investigate students’ perceptions of the TBLT approach, students’ motivations, needs and desired outcomes in order to develop task-based syllabi. This article also addresses the challenges of responding to the needs of a diverse student population in order to determine thematic content and to design the authentic real-life tasks that would appeal to different individual students while taking into account the sociolinguistic and cultural context of the Francophone province of Quebec.The NA consisted of an analysis of the Common European Framework of Reference for Languages (CEFR), an online questionnaire given to both students (n = 48) and teachers (n = 8), and semi-structured interviews with students (n = 8). Despite the apparent heterogeneity of the participants in the two general purpose oral communication language classes, results suggest common, domain-independent goals and themes that would sufficiently cater to the needs and objectives of each individual in the group while also meeting the academic requirements of a university-level course.